ANALISIS EFEKTIVITAS PELAKSANAAN PEMUNGUTAN RETRIBUSI PENGUJIAN KENDARAAN BERMOTOR DI KOTA DENPASAR - I Made Endra Lesmana Putra (Jurnal Widya Akuntansi dan Keuangan, 2019)
Regional Regulation number 20 of 2011 concerning vehicle levies requires every vehicle operating in general to be roadworthy in order to provide a sense of security and comfort for the community. This levy is borne by the community because in the current era of regional autonomy, the regions are given greater authority to regulate and manage their own households as stipulated in Law No.23 of 2014 concerning Regional Government. The purpose of this study was to test the effectiveness of collecting motor vehicle test fees in the city of Denpasar from 2015-2018.The results of the study show that from 2015 to 2018 the realization of levies collection of vehicle testing always exceeds the budget target with a percentage above 100% which is very effective even though the achievement is still fluctuating up and down because the number of vehicles decreases and regulations change, but on average collection of motorized vehicle testing fees still shows very effective.